2011
DOI: 10.3390/molecules16043391
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation of Bioactive Alkaloid Contents in Macleaya microcarpa (Maxim.) Fedde

Abstract: Macleaya microcarpa (Maxim.) Fedde belongs to the genus Macleaya, family Papaveraceae. Together with the better known and more frequently studied species M. cordata (Willd.) R. Br. it is a main source of quaternary benzo[c]phenanthridine alkaloids. Using HPLC we determined the content of eight isoquinoline alkaloids in the aerial and underground parts of 1-, 2-, 12- and 13-year old plants and followed their changes during the vegetative period. The dominant alkaloid of all samples collected in the end of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…PRO exhibited exactly the opposite trend, as it is a biosynthetic precursor of SA and CR (Tanahashi & Zenk, 1990). Similar behaviours were reported in the analysis of the aerial parts of Macleaya microcarpa Fedde (Pěnčíková et al, 2011).…”
Section: Aerial Partsupporting
confidence: 75%
See 1 more Smart Citation
“…PRO exhibited exactly the opposite trend, as it is a biosynthetic precursor of SA and CR (Tanahashi & Zenk, 1990). Similar behaviours were reported in the analysis of the aerial parts of Macleaya microcarpa Fedde (Pěnčíková et al, 2011).…”
Section: Aerial Partsupporting
confidence: 75%
“…An inter-species comparison shows that the amount of MA in a one-year old plant was equivalent to that found in the roots of M. microcarpa 13 years old (Pěnčíková et al, 2011). The levels of MA in the roots of both cultures indicated a maximum at the midpoint of the vegetation cycle, unlike in the aerial part where few maxima were observed.…”
Section: Rootsmentioning
confidence: 91%
“…Many studies have demonstrated that several alkaloids, including benzophenanthridine, protopine, dihydrobenzophenanthridine and protoberberine (shown in Fig. ), are the major bioactive components in the plant . These alkaloids have several reported biological activities including anti‐bacterial, anti‐microbial, anti‐inflammatory, insecticidal, anti‐cancer, anti‐HIV and animal growth promotion .…”
mentioning
confidence: 99%
“…1), are the major bioactive components in the plant. [2][3][4] These alkaloids have several reported biological activities including anti-bacterial, anti-microbial, antiinflammatory, insecticidal, anti-cancer, anti-HIV and animal growth promotion. [5][6][7][8][9][10] Moreover, a set of products (e.g.…”
mentioning
confidence: 99%
“…Capsules are suborbicular. There is only one seed, which is basifixed, erect, and ovoid (Pěnčíková, Urbanová, Musil, Táborská, & Gregorová, 2011;Zhang & Grey-Wilson, 2008).…”
Section: Botanical Characterization and Distributionmentioning
confidence: 99%